The effect of inflation and interest rate on profitability of PT Bank BNI period 2010-2020 - Hendiarto, R Susanto; Gunawan, Delia Anastasya (Jurnal Mantik, 2024)
This research was conducted to examine macroeconomic factors as measured by inflation and interest rates on Return On Assets (ROA) of Bank Negara Indonesia (BNI) for the period 2010 to 2020. This type of research uses a quantitative approach which focuses on hypothesis testing, the data used must be measurable, and will produce generalizable conclusions. The sample in this research is PT Bank BNI in 2010-2020. The data analysis technique used in this study is multiple linear regression analysis, where the data has been tested by testing classical assumptions including data normality, multicollinearity, heteroscedasticity, and autocorrelation. During the observation period between 2010-2020, it shows that the research data is normally distributed. Based on data normality, multicollinearity, heteroscedasticity, and autocorrelation tests, no variables were found that deviated from the classical assumptions. This shows that the available data meets the requirements using multiple linear regression. The results of this study indicate that the inflation and interest rate variables have no significant effect on PT Bank BNI's ROA in 2010-2020.